STRUCTURAL AND COMPOSITIONAL CHARACTERIZATION OF HYDROXYAPATITE AND NANO-CHITOSAN SYNTHESIZED FROM PINCTADA MAXIMA SHELL WASTE FOR BIOMEDICAL APPLICATIONS - Susi Rahayu; D J D H Santjojo; Rahadi Wirawan; Weny Yulianingsih; Masruroh Masruroh (Universitas Mataram, 2026)
Pearl oyster (Pinctada maxima) aquaculture in West Nusa Tenggara (NTB), Indonesia, generates underutilized shell waste that may impact coastal environments. This study aimed to convert the Pinctada maxima shell waste into high-value biomaterials, specifically hydroxyapatite (HA) and nano-chitosan, and to characterize their physicochemical properties for potential biomedical applications. HA was synthesized via the wet precipitation method followed by calcination at 1000 °C and 1100 °C. Concurrently, nano-chitosan was prepared through ionic gelation, investigating the effect of 70% and 80% NaOH alkaline treatments. Characterization of HA using EDX indicated a stable Ca/P molar ratio of 1.68 ± 0.03 (1000°C) and 1.67 ± 0.03 (1100°C), FTIR confirmed the presence of hydroxyl and phosphate groups, and XRD revealed well-defined crystalline structures. For nano-chitosan, particle size analysis (PSA) showed size ranges from 235.55 ± 43.90 up to 2728.58 ± 258.74 nm (70% NaOH) and 20.63 ± 18.04 up to 3525.55 ± 13.06 nm (80% NaOH), with FTIR confirming successful ionic cross-linking. The degree of deacetylation (DD) was found to be high, 81.13 ± 0.03% and 82.65 ± 0.15% respectively, although the XRD patterns indicated a predominantly amorphous structure for the nano-chitosan. These findings suggest that the synthesized HA and nano-chitosan from Pinctada maxima shell waste possess favorable physicochemical characteristics, thus supporting their potential as sustainable materials for various biomedical applications.